FEMININITY PORTRAYED IN DANTE CHARACTER IN ARISTOTLE AND DANTE DISCOVER THE SECRET OF UNIVERSE NOVEL - Handayanti, Diah; Surya, Satyawati; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
The purposes of this research were to find the femininity characteristics and identity developments as a homosexual in the character of Dante of Aristotle and Dante Discover the Secret of Universe novel. This research was categorized as descriptive qualitative research and was using content analysis approach. The researcher used Aristotle and Dante Discover the Secret of Universe novel as the source of data. The data were taken from the dialogues between characters and narrations that indicating Dante’s femininity characteristics based on Bem theory and his identity development as a homosexual based on Cass theory. From the finding of this research, it reveals that the character of Dante possess 16 out of 20 femininity characteristics which are affectionate, cheerful, childlike, compassionate, eager to soothe hurt feelings, feminine, gentle, gullible, sensitive of the needs of others, loyal, soft spoken, sympathetic, tender, understanding, warm, and yielding. Dante also fulfills 4 out of 6 identity developments which are identity of confusion, comparison, tolerance and acceptance. The character of Dante has femininity characteristics and he experiences the identity development phases to be a homosexual.